2022
DOI: 10.3389/fvets.2022.892297
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Outcome in Dogs With Appendicular Osteosarcoma Following Hypofractionated Palliative Radiation Therapy With or Without Bisphosphonates: 165 Cases (2010–2019)

Abstract: ObjectiveTo report the survival times in dogs that received a standardized palliative-intent radiation therapy (RT) protocol for the treatment of canine appendicular osteosarcoma (OSA), alone or in combination with bisphosphonates (BPs), and to determine whether the addition of BPs affects survival. A secondary objective was to identify prognostic features that may influence outcome in dogs undergoing treatment.DesignRetrospective case series.Materials and MethodsDogs with presumed or confirmed OSA of the appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Even if the aesthetic result might be shocking at first, the functional result is good even in large breed dogs in which this neoplasia is frequently diagnosed [59,60]. Each case should be carefully and globally evaluated to understand if a dog might be a good candidate for surgery: amputations can be contra-indicated by severe obesity, concurrent orthopedic or neurological conditions, metastatic disease, and non-compliance of owners [61]. In these cases (or when owners refuse amputation), a limb sparing surgery can be performed or radiation could be applied, alone or in combination with analgesics administration, with the final aim to promote a good quality of life and reducing tumor-related clinical signs [57,61,62].…”
Section: Conventional Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if the aesthetic result might be shocking at first, the functional result is good even in large breed dogs in which this neoplasia is frequently diagnosed [59,60]. Each case should be carefully and globally evaluated to understand if a dog might be a good candidate for surgery: amputations can be contra-indicated by severe obesity, concurrent orthopedic or neurological conditions, metastatic disease, and non-compliance of owners [61]. In these cases (or when owners refuse amputation), a limb sparing surgery can be performed or radiation could be applied, alone or in combination with analgesics administration, with the final aim to promote a good quality of life and reducing tumor-related clinical signs [57,61,62].…”
Section: Conventional Therapiesmentioning
confidence: 99%
“…Bisphosphonates have also been tested alone or in association with palliative-intent radiotherapy: bisphosphonates are synthetic analogs of pyrophosphate with a high affinity for bone material and are able to inhibit osteoclast activity, limiting osteolysis and primary bone lesions [66]. Data reported in a retrospective study suggested that no difference could be found in dogs treated with radiotherapy, with or without the concomitant administration of bisphosphonate [61].…”
Section: Conventional Therapiesmentioning
confidence: 99%